1994
DOI: 10.1515/hfsg.1994.48.4.343
|View full text |Cite
|
Sign up to set email alerts
|

FT-IR Study of the Effect of Irradiation Wavelength on the Colour Reversion of Thermomechanical Pulps

Abstract: The effect of irradiation by light of wavelengths 270, 320, 390 and 500nm on the colour reversion of unbleached and bleached thermomechanical pulp was monitored by FT-IR transmission spectroscopy. The aromatic ring structure in lignin and the C-O and C-H bonds in the wood carbohydrates decreased much more rapidly at shorter irradiation wavelengths for bolh unbleached and bleached pulp samples. The rate of decrease of aromatic ring and guaiacyl structures is the same at all wavelengths for the unbleached pulp, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…3-5. Lignin decay and carbohydrate loss as a consequence of UV irradiation of wood pulp were shown by Kimura et al [33,34]. Furthermore, they demonstrated that, the decay of the lignin functionality is combined with the formation of aliphatic carbonyl groups.…”
Section: Vibrationsmentioning
confidence: 94%
“…3-5. Lignin decay and carbohydrate loss as a consequence of UV irradiation of wood pulp were shown by Kimura et al [33,34]. Furthermore, they demonstrated that, the decay of the lignin functionality is combined with the formation of aliphatic carbonyl groups.…”
Section: Vibrationsmentioning
confidence: 94%
“…The difference in photostability between oxidatively (hydrogen peroxide) bleached and reductively (dithionite, bisulfite) bleached pulps is not fully understood, and different opinions regarding the effect of reductive and oxidative bleaching exist (Jansen and Lorås 1968;Abou-State 1976;Janson and Forskåhl 1991;Janson 1993;Kuys and Abbot 1996;Forsskåhl 2000). The discrepancy in reported observations could be due to differences in exposure conditions, light sources, exposure times, grammage of the exposed samples, and procedures chosen for quantifying the color reversion (Schmidt and Heitner 1993a;Kimura et al 1994;Paulsson and Ragauskas 1998b).…”
Section: Factors Affecting Light-induced Yellowingmentioning
confidence: 98%
“…7, and the assignment of bands in the ATR-FTIR spectra is listed in Table 1 (Kimura et al 1994;Kimura et al 1995;Pandey 1999;Tshabalala et al 2005;Rosu et al 2010). As shown in Fig.…”
Section: Atr-ftir Analysis Spectra Analysis Before and After Bleachingmentioning
confidence: 99%
“…Lignin is known to be responsible for yellowing. Over the last several decades, the color reversion of mechanical pulps has been studied by many researchers (Kimura et al 1994;Leary 1994;Müller et al 2003;Zou 2004;Pandey 2005;Rosu et al 2010), but the underlying mechanism of photo yellowing has yet to be discovered. Moreover, the studies on the yellowing of deinked pulp, especially on the comparison of Mg(OH)2-based with NaOH-based hydrogen peroxide bleached pulp, were much fewer (Savoye et al 2011).…”
Section: Introductionmentioning
confidence: 99%